Pertuzumab, trastuzumab, and docetaxel for HER2-positive metastatic breast cancer (CLEOPATRA): end-of-study results from a double-blind, randomised, placebo-controlled, phase 3 study. Issue 4 (April 2020) - Swain, Sandra M; Miles, David; Kim, Sung-Bae; Im, Young-Hyuck; Im, Seock-Ah; Semiglazov, Vladimir; Ciruelos, Eva; Schneeweiss, Andreas; Loi, Sherene; Monturus, Estefanía; Clark, Emma; Knott, Adam; et al.
Summary: Background: CLEOPATRA was a phase 3 study comparing the efficacy and safety of pertuzumab, trastuzumab, and docetaxel with placebo, trastuzumab, and docetaxel in patients with HER2-positive metastatic breast cancer. In the primary analysis and subsequent reports, progression-free and overall survival were significantly improved in the pertuzumab group compared with the placebo group. Here, we report the end-of-study analysis of CLEOPATRA. Methods: This was a double-blind, randomised, placebo-controlled, phase 3 trial that was done at 204 centres in 25 countries. Eligible patients were 18 years or older, had HER2-positive, metastatic breast cancer, had not received previous chemotherapy or biological treatment for their metastatic disease, and had an Eastern Cooperative Oncology Group performance status of 0 or 1. All study drugs were given intravenously, every 3 weeks. Patients were assigned to receive either pertuzumab or placebo at a loading dose of 840 mg, and 420 mg thereafter; plus trastuzumab at 8 mg/kg loading dose and 6 mg/kg thereafter; and docetaxel at 75 mg/m 2, escalating to 100 mg/m 2 if tolerated. Pertuzumab or placebo and trastuzumab were given until disease progression; docetaxel was given for six cycles, or longer at the investigators' discretion. Randomisation (1:1) was done by use of an interactive voice-response system and was stratified by geographical region (Asia, Europe, North America, or South America) and previous treatment (previous adjuvant or neoadjuvant chemotherapy vs none). The primary endpoint was independent review facility-assessed progression-free survival, which has been reported previously. Since the confirmatory overall survival analysis had also occurred before this prespecified end-of-study analysis, analyses presented here are descriptive. Overall survival analyses were based on the intention-to-treat population with crossover patients analysed in the placebo group; analyses were not adjusted for crossover to the pertuzumab group and are likely to be conservative. Safety analyses were based on treatment received; crossover patients were counted in the placebo group up to the day before first pertuzumab dose. This trial is registered with ClinicalTrials.gov, number NCT00567190 . Findings: Between Feb 12, 2008, and July 7, 2010, 1196 patients were assessed for eligibility, of whom 808 were enrolled and randomly assigned. 402 patients were assigned to receive docetaxel plus trastuzumab plus pertuzumab, and 406 patients were assigned to receive docetaxel plus trastuzumab plus placebo. Clinical cutoff for this analysis was Nov 23, 2018. Between July 2012 and clinical cutoff, 50 patients crossed from the placebo to the pertuzumab group. Median follow-up was 99·9 months in the pertuzumab group (IQR 92·9–106·4) and 98·7 months (90·9–105·7) in the placebo group. Median overall survival was 57·1 months (95% CI 50–72) in the pertuzumab group and 40·8 months (36–48) in the placebo group (hazard ratio 0·69, 95% CI 0·58–0·82); 8-year landmark overall survival rates were 37% (95% CI 31–42) in the pertuzumab group and 23% (19–28) in the placebo group. The most common grade 3–4 adverse event was neutropenia (200 [49%] of 408 patients in the pertuzumab group, 183 [46%] of 396 patients in the placebo group). Five (1%) of 408 patients in the pertuzumab group and six (2%) of 396 patients in the placebo group had treatment-related deaths. One new serious adverse event suggestive of congestive heart failure (pertuzumab group) and one new symptomatic left ventricular systolic dysfunction (post-crossover) occurred since the previous analysis. Interpretation: Our analysis shows that the previously observed improvements in overall survival with pertuzumab, trastuzumab, and docetaxel versus placebo, trastuzumab, and docetaxel were maintained after a median of more than 8 years of follow-up. The long-term safety and cardiac safety profiles of pertuzumab, trastuzumab, and docetaxel were maintained in the overall safety population and within crossover patients. HER2-targeted therapy has changed the natural history of HER2-positive metastatic breast cancer, with the dual blockade of pertuzumab and trastuzumab, with docetaxel, demonstrating an 8-year landmark overall survival rate of 37%. Funding: F Hoffmann-La Roche and Genentech.